Indeterministic worlds of Franz-Serafin Exner and Marian Smoluchowski - Rodzeń, Jacek (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2017)
The paper presents philosophical views which have been propagated in the first decade of the 20th-century by Austrian experimental physicist Franz-Serafin Exner (1846-1926). According to Exner all apparently deterministic laws are only a kind of the macroscopic limit of the indeterministic random events and processes in nature. The paper attempts to show whether Exner’s ideas have influenced the views on randomness and probability developed by renowned Polish physicist Marian Smoluchowski (1872-1917) who belonged to informal circle of Exner’s students and assistants (so-called Exner-Kreis).